2017
DOI: 10.1093/carcin/bgx063
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases: their functional role in lung cancer

Abstract: Lung malignancy is the foremost cause of cancer-related deaths globally and is frequently related to long-term tobacco smoking. Recent studies reveal that the expression of matrix metalloproteinases (MMPs) is extremely high in lung tumors compared with non-malignant lung tissue. MMPs are zinc-dependent proteases and are involved in the degradation of extracellular matrix (ECM). Several investigations have shown that MMPs manipulate the activity of non-ECM molecules, including cytokines, growth factors and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 164 publications
2
113
2
1
Order By: Relevance
“…MMPs are abundantly detected in numerous malignant neoplasms and have critical implications in almost all stages of tumour progression [2]. Recent studies have shown that aberrant MMP expression is associated with the invasion and metastasis of several malignant tumours (colorectal [3], prostate [4], liver [5], breast [6], retinoblastoma [7], and lung [8]) both in vitro and vivo. Among the MMPs, MMP7 (aka matrilysin1) is the smallest secreted proteolytic enzyme, lacking the C-terminal hemopexin domain compared with other family members, with a wide spectrum of substrate specificity against ECM components, including laminin, type IV collagen, fibronectin, and proteoglycans [9,10], as well as other molecules, such as E-cadherin, β4 integrin, tumour necrosis factor-α, and the Fas ligand [11].…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are abundantly detected in numerous malignant neoplasms and have critical implications in almost all stages of tumour progression [2]. Recent studies have shown that aberrant MMP expression is associated with the invasion and metastasis of several malignant tumours (colorectal [3], prostate [4], liver [5], breast [6], retinoblastoma [7], and lung [8]) both in vitro and vivo. Among the MMPs, MMP7 (aka matrilysin1) is the smallest secreted proteolytic enzyme, lacking the C-terminal hemopexin domain compared with other family members, with a wide spectrum of substrate specificity against ECM components, including laminin, type IV collagen, fibronectin, and proteoglycans [9,10], as well as other molecules, such as E-cadherin, β4 integrin, tumour necrosis factor-α, and the Fas ligand [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, nonspecific phagocytic cells, such as epithelial cells and fibroblasts, are more effective in removing cell debris than specific phagocytic cells, such as macrophages and dendritic cells. Furthermore, MMPs are closely involved in the induction of lung cancer, fibrosis, and apoptotic cell death, and can contribute to host defense through the cleavage of membrane‐bound receptor protein . In this study, Kathon induced apoptotic and necrotic cell death accompanied by the increased release of MMP‐1 and MMP‐3 at 24 h after exposure to bronchial epithelial cellsKathon also increased the total number of cells in the lung on day 14 after a single instillation.…”
Section: Discussionmentioning
confidence: 54%
“…MMPs are involved in matrix degradation and play key roles in tumor growth, invasion and angiogenesis (33,34). c-Jun is a major transcription factor, which regulates the expression of MMPs (35).…”
Section: Discussionmentioning
confidence: 99%